Microscope studies of symptomless growth of Botrytis cinerea in Lactuca sativa and Arabidopsis thaliana - Emmanuel, C.J.; Schoonbeek, H.J.; Shaw, M.W. (Wiley, 2022)
The grey mould pathogen Botrytis cinerea forms systemic associations in some hosts, spreading into plant organs produced a considerable time after initial infection. These infections may have no macroscopic symptoms during much of the hosts' lifetime and are at least partially within the host tissue. The aim of the studies reported here was to locate and visualize these infections at a cellular level in Lactuca sativa (lettuce) and Arabidopsis thaliana. Symptomless but infected plants were produced by dry spore inoculation of plants growing in conditions previously shown to result in fungal spread from the initial inoculation site to newly developing plant organs. Tissue taken from inoculated plants was examined using confocal laser scanning microscopy. Two B. cinerea isolates were used: B05.10 and its GFP-labelled derivative Bcgfp1-3. Spore ger mination on leaf surfaces was followed by development of subcuticular inclusions and plant cell damage in single infected epidermal cells and sometimes a few nearby cells. Sparsely branched long hyphae arose and spread from the inclusions, mostly on the outer surface of the epidermal layer but occasionally below the cuticle or epidermal cells, where further inclusions formed. This was consistent with the pattern in time of recovery of B. cinerea from surface-sterilized leaf tissue. In the late symptomless phase, mycelium arising from internal fungal inclusions formed mycelial networks on the surface of leaves. Symptomless exterior mycelium grew on the roots in A. thaliana.
Keywords: Confocal microscopy; Endophyte; Grey mould; Latent infection; Lettuce